Infatuation in Spark's 'The Notebook' (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2020)
This research is conducted to analyze the infatuation that occurs to the main character, Noah Calhoun in Nicholas Sparks The Notebook. The objective of this research is to describe the main character and the conflicts in Sparks’s The Notebook. It also reveals the main character infatuation and desire based on the concept of psyche using Lacanian psychological approach. This research uses qualitative-descriptive research to answer the question about the infatuation that occurs to the main character and it explains in the form of words. The research results in several findings as follows: 1) the infatuation described in Spark’s The Notebook can be seen through its intrinsic element especially the character and the conflict. The main character, Noah Calhoun is described as a patient, kind, and faithful man. The conflict and the struggle Noah faces through Allie and her family show how Noah cannot move on from Allie. 2) The infatuation occurs to Noah Calhoun show by the concept of psyche using the Lacanian Psychology approach. Based on Noah's concept of psyche analysis tell that the main character, Noah Calhoun is feeling lacks and always looking for Allie to complete his lacks. The main character's psychological development toward his first love brings out the desire to be loved and have his relationship back. The desire tells that Allie is the one Noah needed in his life. Keywords: infatutation, Lacanian theory, Psychological approach, The Notebook